A Two-Phase Pilot Study to Evaluate the Safety and Tolerability of an In Situ Polymerizing Collagen. Issue 9 (September 2017) - Inglefield, Christopher; Rone-McCrate, Rebecca; Brooks, Robert; Zhu, Jiaxun; Grant, Sheila; DeVore, Dale P.
Abstract : BACKGROUND: Demand for collagen-based fillers has declined primarily because of limited long-term clinical benefit and the introduction of hyaluronic acid compositions. In situ polymerizing collagen is a noncrosslinked solution of porcine collagen containing a collagenase shield that undergoes fibrillogenesis on injected into tissues forming a natural matrix. OBJECTIVE: Conduct a prospective, single-center, dual-phase open-label study in 8 subjects to evaluate the safety, tolerability, and efficacy of the porcine collagen composition. METHODS: In Phase I, potential hypersensitivity of the collagen composition was evaluated after skin testing in the back (men) or forearms of subjects (women). In Phase II, subjects showing no signs of hypersensitivity received collagen injections into the nasolabial area followed by evaluation at 1, 4, 8, and 12 weeks using the Global Aesthetic Improvement Scale. RESULTS: None of the subjects had signs of hypersensitivity and all continued in Phase II. The treating physician(s) reported no post-treatment adverse events. Improvement of the nasolabial fold was observed by the physicians and confirmed by assessment of high-resolution photographs and Global Aesthetic Improvement Scale scores over the 12-week treatment were maintained. CONCLUSION: In this pilot clinical study in situ polymerizing collagen was shown to be safe and effective throughout the 3-month study period.